2022
DOI: 10.7759/cureus.21848
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Pattern and Severity of Adverse Events Following Immunization (AEFIs) Associated With Chadox1 nCOV-19 Corona Virus Vaccine (Recombinant) Among the Healthcare Workers of a Tertiary Care Institute of Eastern Uttar Pradesh, India

Abstract: BackgroundIn January 2020, the Government of India based on the recommendation of the Drugs Controller General of India (DCGI) and National Technical Advisory Group on Immunization (NTAGI) started the rollout of the COVID-19 vaccine in the country. Two vaccines, ChAdOx1 nCoV-19 coronavirus vaccine (recombinant), i.e., COVISHIELD produced by Serum Institute of India and COVAXIN developed indigenously by Bharat Biotech, were given emergency use authorisation (EUA) by the DCGI. MethodsIn this cohort study, we ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
2
1
2
1
Order By: Relevance
“…Symptoms of AEFI mostly appear on the same day after receiving the first dose and recover within 1–4 days. This finding is slightly different from findings of other COVID-19 inactivated virus vaccine that reports that many AEFIs occur in 1–7 days and recover in 2 days ( 13 , 24 , 35 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Symptoms of AEFI mostly appear on the same day after receiving the first dose and recover within 1–4 days. This finding is slightly different from findings of other COVID-19 inactivated virus vaccine that reports that many AEFIs occur in 1–7 days and recover in 2 days ( 13 , 24 , 35 ).…”
Section: Discussioncontrasting
confidence: 99%
“…However, no severe symptoms found ( 36 ). Another study in the community also found the same results for the symptoms, although it was conducted in an older age ( 26 , 35 ).…”
Section: Discussionsupporting
confidence: 61%
“… 45 The available clinical trial data for various COVID-19 vaccines support our findings that reported side effects were mild/moderate, self-limiting, and did not require any further treatment. 44 , 46–52 As in other studies of HCWs in India, 37–40 , 53 Nepal, 41 , 42 and Bangladesh, 16 most of our respondents experienced mild to moderate symptoms (93.4%), which were self-limiting and resolved within a few days.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, an observational study on surveillance of adverse events of Covishield conducted by Dhanya Jose et al [ 15 ], a cross-sectional study conducted on ADRs of Covishield by Sukhpal Kaur et al [ 16 ], A comparative study conducted on adverse events of Covishield by Sushil Rayamajhi et al [ 17 ] has shown the ADRs of fever, headache, weakness, pain at the injection site as the most common ADRs of Covishield which were similar to our studies. However, the data was different in the research reported by Dr Rajeev et al [ 18 ] and a study conducted at the tertiary care institute of Eastern Uttar Pradesh by Bhushan Kamble et al [ 19 ], which showed that Myalgia and tiredness were high.…”
Section: Discussioncontrasting
confidence: 57%